1985
DOI: 10.1042/bj2310097
|View full text |Cite
|
Sign up to set email alerts
|

Stromal protein phosphorylation in spinach (Spinacia oleracea) chloroplasts

Abstract: When intact spinach chloroplasts were supplied with [32P]Pi, stromal protein phosphorylation was found to occur in the dark. On illumination the thylakoid protein kinase was activated and the amount of label found in thylakoid proteins quickly exceeded that incorporated into stromal protein, such that the latter was found to account for only 10-15% of the total radioactivity bound to chloroplast proteins after 5 min illumination. The rate of phosphorylation of stromal polypeptides was unchanged by light. After… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Many stromal proteins undergo reversible phosphorylation (Foyer, 1985), and the stromal protein phosphatase, along with other unidentified protein phosphatases, could catalyze the dephosphorylation of some or a11 of these proteins. The results of our experiment in which we examined the dephosphorylation of the major stromal phosphoprotein may not be conclusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many stromal proteins undergo reversible phosphorylation (Foyer, 1985), and the stromal protein phosphatase, along with other unidentified protein phosphatases, could catalyze the dephosphorylation of some or a11 of these proteins. The results of our experiment in which we examined the dephosphorylation of the major stromal phosphoprotein may not be conclusive.…”
Section: Discussionmentioning
confidence: 99%
“…dephosphorylation in the chloroplast has focused mainly on the LHC-I1 (Bennett, 1977), although many thylakoid proteins (Markwell et al, 1984;Silverstein et al, 1993) and stromal proteins (Foyer, 1985) become phosphorylated. The reversible phosphorylation of LHC-I1 is coincident with the state 1 to state 2 transition governing photosynthetic quanta1 energy distribution (Allen, 1995).…”
mentioning
confidence: 99%
“…Mann and Turner (1988) have shown that the large subunit of Rubisco is phosphorylated on Tyr residues in Rhodomicrobium vannielii. The phosphorylation of this subunit may be involved in the assembly of Rubisco (Foyer, 1985). When ABA inhibits germination, the dephosphorylation on Tyr residues of the large subunit of Rubisco could impair the assembly of the enzyme.…”
Section: Germination-related Proteins Involved In the Mobilization Ofmentioning
confidence: 99%
“…Phosphorylation/inactivation of PDC and PPDK has also been established in situ (6,24). In contrast, phosphorylation of Rubisco has unknown effects on the enzyme (12). Data on hydroxymethyl glutaryl CoA reductase have indicated that it may also be phosphorylated (25 Immunoblots.…”
mentioning
confidence: 99%
“…To our knowledge, only three specific soluble leaf proteins have been identified as being phosphorylated: pyruvate dehydrogenase complex (PDC3; [24]), PPDK (1,9), and the large and small subunits of Rubisco (12). Phosphorylation of the mitochondrial 2 Present address: Department of Biochemistry, 21 1 Schweitzer Hall, University of Missouri, Columbia, MO 6521 1. I Abbreviations: PDC, pyruvate dehydrogenase complex; PPDK, pyruvate, Pi dikinase; PEP, phosphoenolpyruvate; PEPCase, PEP carboxylase; AP5A, P'P5-di(adenosine-5')pentaphosphate; IEF, isoelectric focusing; Rubisco, ribulosebisphosphate carboxylase/oxygenase.…”
mentioning
confidence: 99%